2015
DOI: 10.1515/fhort-2015-0023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of polychlorinated biphenyl degradation through refuse from Pleurotus ostreatus, Lentinula edodes and Agaricus bisporus production

Abstract: White rot fungi (WRF) are known to have the ability to degrade organic pollutants with a structure similar to lignin. Because of this, the degradation of polychlorinated biphenyls (PCBs) congeners no. 28, 52, 101, 138, 153 and 180 by substrate before fruiting (substrate) and/or after fruiting (SMS) from cultivated mushrooms Pleurotus ostreatus, Lentinula edodes and Agaricus bisporus was examined. The experiment was carried out in four replications for each treatment using a mixture of substrate/SMS and sandy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that native fungal species might be more efficient at degrading and utilizing PCBs than standard species (Sage et al 2014). As noted by Gąsecka et al (2015), A. bisporus could dechlorinate PCB congener over time, for instance, PCB-52 (46-75%), PCB-28 (41-68%), PCB-101 (32-70%), PCB-138 (25-59%), PCB-153 (22-57%), and PCB-180 (17-59%). Furthermore, Périgon et al (2019) have recently provided evidence that five different fungal species demonstrated substantive PCB degradation efficiencies, which varied between 79.86% for Thermothelomyces heterothallica and soared up to 95.91% for Thermoascus crustaceus.…”
Section: Identification Of Isolated Pcb-degrading Fungi and Their Deg...mentioning
confidence: 82%
See 1 more Smart Citation
“…Previous studies have shown that native fungal species might be more efficient at degrading and utilizing PCBs than standard species (Sage et al 2014). As noted by Gąsecka et al (2015), A. bisporus could dechlorinate PCB congener over time, for instance, PCB-52 (46-75%), PCB-28 (41-68%), PCB-101 (32-70%), PCB-138 (25-59%), PCB-153 (22-57%), and PCB-180 (17-59%). Furthermore, Périgon et al (2019) have recently provided evidence that five different fungal species demonstrated substantive PCB degradation efficiencies, which varied between 79.86% for Thermothelomyces heterothallica and soared up to 95.91% for Thermoascus crustaceus.…”
Section: Identification Of Isolated Pcb-degrading Fungi and Their Deg...mentioning
confidence: 82%
“…The level of chlorination of biphenyl rings is not necessarily the limiting factor in fungal-mediated PCB degradation (Federici et al 2012;Mouhamadou et al 2013). Many factors, such as fungal species, initial concentration, incubation duration, and substrate classification, dictate the pace of PCB biodegradation (Kubátová et al 2001;Gąsecka et al 2015).…”
Section: Identification Of Isolated Pcb-degrading Fungi and Their Deg...mentioning
confidence: 99%
“…An oxygen concentration of 10% inside the substrate combined with 10% CO 2 also had no influence on the degradation potential of P. ostreatus. Monika et al [64] carried out an experiment using a mixture of substrate/SMS and sandy soil with PCBs. The results indicated that degradation was dependent on substrate/SMS addition, the concentration of PCBs, and time of incubation.…”
Section: P Ostreatus Based Degradation Of Pcbs: Milestones Achievedmentioning
confidence: 99%
“…The SMS of P. ostreatus as explained in the previous section, which showed extensive PAH removal activity, is an area worth developing on with respect to PCBs. The SMS of P. ostreatus has been limited to a single study [64] for PCB degradation. This study showed that the differences between PCB degradation by substrate and SMS of P. ostreatus were very weak; hence, they suggested that it is possible to use SMS for the decontamination of PCB polluted soil.…”
Section: P Ostreatus-based Degradation Of Pcbs: Future Prospectsmentioning
confidence: 99%